The problem of ethnic identity in the context of globalization (Journal of Philosophy Culture and Political Science, 2018)
Each epoch proposes certain issues. The main challenge of the modern era are two interrelated problems of identity and globalization. Globalization is the General global process and has many different directions from political and economic to the level and way of life of an individual and of the nation and society in General, is a complex cross-border interactions between individuals, institutions, companies and markets. The emergence of new forms of relationship and interaction between countries and people under the influence of globalization entails rethinking the established views on the different kinds of identities and their coexistence. Moreover, the picture of globalization consequences would be incomplete without lighting situation related to cultural identity. In the conditions of globalization of the transformation and pluralization identity. Under the influence of globalization, cross-cultural communication of the countries and peoples transformed radically, resulting in a drift of socio-cultural identity. Key words: globalization, identity, ethnicity ,traditions, unification, threat, culture, integration.